Effect of Forced Liquid Cooling on the Voltage/Charge Displacement Characteristics of Stacked Piezoelectric Actuators during High-Frequency Drive - Rina Nishida (MDPI AG, 2021)
Piezoelectric stack actuators (PESAs) are widely used in applications requiring a fast response, high resolution, and high accuracy. The self-heating of a PESA during continuous drive with a large amplitude at high frequencies can change its voltage displacement and charge displacement characteristics. These changes can lead to a loss of stability and inaccurate PESA positioning systems. In this paper, we confirmed that by using our proposed forced liquid cooling, the changes to the dynamic characteristics and the impedance of a PESA due to the fact of self-heating could be reduced. Voltage displacement curve measurements at 10 kHz demonstrated that with natural heat dissipation, the amplitude of PESA increased by 15% due to the self-heating compared to the amplitude measured at the start of driving but only by 3% with forced liquid cooling. The displacement-to-charge ratio decreased by 12% compared to that at room temperature with natural heat dissipation, while it increased by 1% during forced liquid cooling. In the measured frequency response of the voltage displacement transfer function, the increased temperature changed the gain and phase of the first and secondary vibration modes above 20 kHz with natural heat dissipation. Forced liquid cooling also reduced the variations in the frequency response of the voltage displacement transfer function.